2021
DOI: 10.15277/bjd.2021.308
|View full text |Cite
|
Sign up to set email alerts
|

Previous structured education attendance and the relationship with HbA1c and hypoglycaemia awareness in people living with type 1 diabetes mellitus using FreeStyle Libre: insights from the Association of British Clinical Diabetologists (ABCD) Nationwide Audit

Abstract: Background: Dose Adjustment For Normal Eating (DAFNE) is the gold standard National Institute for Health and Care Excellence (NICE) recommended structured education programme that promotes self-management in people living with type 1 diabetes (T1D). We have recently shown that FreeStyle Libre (FSL) is associated with improved haemoglobin A1c (HbA1c) and hypoglycaemia awareness. Aims: To explore the effect of structured education including DAFNE on HbA1c and GOLD score when combined with FSL use. Methods: The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…The baseline GOLD score (to assess hypoglycaemia awareness) was 2.7 (±1.8), which improved to 2.4 (±1.7) ( p < 0.0001) at follow‐up. Furthermore, we showed that FSL users reported a reduction in diabetes‐related distress (using the 2‐point Diabetes Distress Screening scale questionnaire – DDS score), hospital admissions, 3 and that the improvement in glycaemic control and hypoglycaemia awareness was independent of structured education attendance 2 . In this study, we explore the impact of long‐term FSL use on glycaemic control, hypoglycaemia awareness and diabetes‐related distress in people living with T1D.…”
Section: Group I Group Ii Group Iii Group Iv Follow‐up <1 Year Follow...mentioning
confidence: 96%
See 3 more Smart Citations
“…The baseline GOLD score (to assess hypoglycaemia awareness) was 2.7 (±1.8), which improved to 2.4 (±1.7) ( p < 0.0001) at follow‐up. Furthermore, we showed that FSL users reported a reduction in diabetes‐related distress (using the 2‐point Diabetes Distress Screening scale questionnaire – DDS score), hospital admissions, 3 and that the improvement in glycaemic control and hypoglycaemia awareness was independent of structured education attendance 2 . In this study, we explore the impact of long‐term FSL use on glycaemic control, hypoglycaemia awareness and diabetes‐related distress in people living with T1D.…”
Section: Group I Group Ii Group Iii Group Iv Follow‐up <1 Year Follow...mentioning
confidence: 96%
“…The FreeStyle Libre (FSL) glucose monitoring system is one such technology. To obtain a glucose reading, the libre reader is held near the sensor, and the device then displays glucose information over the preceding 8 h, which includes current glucose and forecasts changes in glucose levels, thus allowing the operator to make necessary adjustments to diet and/or insulin dosing 1,2 . In clinical practice, the FSL monitoring system was first introduced in 2014.…”
Section: Group I Group Ii Group Iii Group Iv Follow‐up <1 Year Follow...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to the assumptions made, our work demonstrated that it did not matter whether somebody had attended structured education or not -HbA1c reduction was seen across the board independent of prior education status. 5 This finding is further supported by the realworld data which showed that during the pandemic lockdown, a period when people with diabetes had limited support from healthcare professionals, there was an improvement in time in range, reflecting improved self-management. 6 Finally, and possibly most importantly, the ABCD audit has also demonstrated that flash glu- cose monitoring is associated with a significant reduction in diabetes-related distress (50% to 26%, p<0.001).…”
mentioning
confidence: 59%